Petrografía, propiedades físicas y durabilidad de rocas utilizadas en el patrimonio monumental de Cataluña, España (2.ª parte) - Esbert, Rosa M.; Marcos, Rosa M.; Ordaz, Jorge; Montoto, Modesto; Alonso, F. Javier; Suarez del Río, Luis M.; Ruiz de Argandoña, Vicente G.; Calleja, Lope; Rodríguez Rey, Ángel (Materiales de Construcción, 1991)
The petrographical description and the values of some physical properties of three rocks used in the Architectonic Heritage of Catalonia (Spain) are presented. These rocks are known, in the field of the "building stones" as Sant Vicenç, El Figueró and Manresa stones. By means of accelerated ageing tests, their durability is evaluated.